Systematic review with meta-analysis: a history of smoking is not associated with a higher risk of pouchitis - KANİ, HALUK TARIK (WILEY, 2020)
Background Ileal pouch-anal anastomosis is a common surgical procedure in patients with an initial diagnosis of ulcerative colitis or indeterminate colitis. Tobacco smoking has been associated with protection from onset of ulcerative colitis. Smoking has been reported to be both a protective factor and a risk factor for the development of pouchitis. Aim To examine the influence of smoking on the risk of pouchitis. Methods We identified 15 studies evaluating smoking as a risk factor for developing pouchitis in ulcerative colitis or indeterminate colitis patients with a history of ileal pouch-anal anastomosis in a systematic search performed from inception through May 4, 2020. A meta-analysis was then performed using a random-effects model to generate risk ratios (RR) and 95% confidence intervals (CI). Results A history of smoking compared with never smoking was not associated with an increased risk of developing pouchitis (RR = 0.94, 95% CI 0.76-1.18,I-2 = 73.7%). There was also no significant risk of pouchitis when comparing current smokers vs nonsmokers (RR = 0.93, 95% CI 0.70-1.24,I-2 = 78.5%) and former smokers vs nonsmokers (RR = 0.96, 95% CI 0.74-1.23,I-2 = 78.5%). Conclusions Smoking, past or present, is not associated with an increased risk for the development of pouchitis in patients with ulcerative colitis or indeterminate colitis.
Keywords: ANAL ANASTOMOSIS; ULCERATIVE-COLITIS; RESTORATIVE PROCTOCOLECTOMY; DISEASE; COMPLICATIONS; PREDICTORS; FREQUENCY; SURGERY